The Administration of Pseudoalteromonas piscisida 1UB through Artemia sp. to Enhance Growth Performance, Immune Response and Resistance of White Shrimp (Litopenaeus vannamei) Larvae against Vibrio harveyi (Indonesian Society for microbiology, 2018)
This study aimed to evaluate the effectiveness of the supplementation of Pseudoalteromonas piscisida 1UBthrough Artemia sp. to enhance the growth performance, immune response and the resistance of white shrimp (Litopenaeus vannamei) larvae to the infection of Vibrio harveyi. The natural feed given to the white shrimp larvae was Artemia sp. enriched with P. piscisida 1UBR at concentrations of 106 CFU mL-1, 107 CFU mL-1, 108 CFU mL-1 and a control (Artemia sp. without any enrichment). The experimental shrimps (0.25±0.02 mg shrimp-1) were reared in the aquarium (25 × 20 × 30 cm) containing 4 L sea water with a stocking density of 30 shrimps L-1. The experimental shrimps were fed the experimental feed from mysis 3 to PL12, and after that they were challenged with V. harveyi (107 CFU mL-1)through an immersion method. The results of this study revealed that the administration of Artemia sp. enriched with P. piscisida 1UB could improve the survival, daily growth rate and absolute growth of length of white shrimp larvae. The activities of protease, lipase and amylase of white shrimp larvae treated with probiotic were higher (p<0.05) than those of the control. After the challenge test, white shrimp larvae treated with probiotic also had better survival and immune response (total hemocyte count, phagocytic activity, phenoloxidase activity and respiratory burst activity) than those of the the positive control. The best results were obtained in the probiotic application with a concentration of 108 CFU mL-1.